Comparing the Effects of Rhythm-Based Music Training and Pitch-Based Music Training on Executive Functions in Preschoolers - Frischen, Ulrike; Schwarzer, Gudrun; Degé, Franziska (Frontiers in Integrative Neuroscience, 2019)
Previous research has indicated beneficial effects of music training on executive functions in children. However, researchers have not clearly determined which component of music training produces these beneficial effects or whether different components exert different effects on executive functions. In the present study, we examined the impact of rhythm-based music training compared to pitch-based music training and sports training as a control on executive functions in preschoolers. Children aged between 5 and 6 years (N = 76) were randomly assigned to one of the three training groups and received training in small groups 3 times a week for 20 minutes in German kindergartens. Before and after training, children completed tests designed to assess inhibition, set shifting, and visuospatial working memory. Parental education, family income, personality, and IQ served as control variables. We observed a significant training group x time interaction for the measure of inhibition. Children from the rhythm group exhibited significant improvements in inhibition from pre- to posttests (dRM = 0.56), whereas children from the other groups did not. Furthermore, children from the rhythm group significantly differed from the sports control group at posttest (dcorr = 0.82). Concerning the measures of set shifting and visuospatial working memory, the descriptive data revealed similar results; however, we did not observe significant training group x time interactions. Based on our findings, rhythm-based music training specifically enhances inhibition in preschoolers and might affect other executive functions, such as set shifting and visuospatial working memory.